Ethical regulation and animal science: why animal behaviour is special - Barnard, Chris (Animal behaviour, 2007)
Like other areas of animal science, the study of animal behaviour is becoming increasingly subject to ethical regulation and legislation. Sensible and well-informed regulation is to be welcomed both on compassionate grounds and because misuse of animals is likely to compromise the science itself. However, it is evident that much of the impetus and direction in the regulation debate is coming from one particular corner of animal science: that concerned with utilitarian and commercial interests taking place in controlled laboratory environments. This is sustained by an overemphasis on potential medical benefits as the perceived key selling point for animal science to a hostile public. Such a bias risks potentially unfortunate consequences for wider aspects of animal science, and is unlikely to serve the best welfare interests of animals when viewed from their own biological perspective. I review some of the concerns that arise from this, and suggest that the study of animal behaviour has a uniquely important role to play both in the development of animal welfare science itself and in the public debate about the regulation of animal science as a whole.